Factors that influence the Quality of Human Resources for Employees at the National Disaster Management Agency - Simanjuntak, Komaruddin; Madhakomala, Madhakomala; Gunawan, Kazan (Journal of International Conference Proceedings, 2023)
This study aims to analyze innovative work behavior at BNPB which will be used in this study to explore and examine the impact of transformational leadership and human resources on the quality of human resources. This research method uses a quantitative approach. The number of samples = 239 BNPB employees was obtained. Data was collected through survey method and analyzed using Structural Equation Modeling with WarpPLS approach. The results of this study found that the transformational leadership variable (X1) that has the highest weight is building the organization. In the innovative work behavior variable (Y1), which has the highest weight is developing ideas. Finally, the variable quality of human resources (Y2) which has the highest weight is continuous learning. Furthermore, there are two relationships whose results are not significant, and one relationship whose results are significant. The relationship between Transformational Leadership on Innovative Work Behavior and Transformational Leadership on Human Resource Quality obtained insignificant results, while the relationship between Innovative Work Behavior on Human Resource Quality obtained significant results for each variable relationship of the three factors